Further information on the origin of the Yale and Oak Ridge wild-type strains of Neurospora crassa - M. E. Case; H. E. Brockman; F. J. de Serres (Fungal Genetics Reports, 1965)
Further information on the origin of the Yale and Oak Ridge wild-type strains of Neurospora crassa